Oxygen Reduction Reaction: Tuning Surface Structure and Strain in Pd–Pt Core–Shell Nanocrystals for Enhanced Electrocatalytic Oxygen Reduction (Small 7/2017). Issue 7 (February 2017) - Xiong, Yalin; Shan, Hao; Zhou, Zhengnan; Yan, Yucong; Chen, Wenlong; Yang, Yaxiong; Liu, Yongfeng; Tian, He; Wu, Jianbo; Zhang, Hui; Yang, Deren
Abstract : In article number 1603423, He Tian, Jianbo Wu, Hui Zhang, and co‐workers develop a thermodynamically controlled method for the epitaxial growth of atomically layered Pt shells on icosahedral, octahedral, and cubic Pd seeds, with Pd‐Pt core‐shell icosahedra being the best electrocatalysts for oxygen reduction reaction. The cover image shows that most of Pt shells in the icosahedra are dominated by compressive strain with a proper size, while compressive and tensile strains co‐exist in Pt shells of the octahedra, which might be responsible for their different catalytic properties.